2018
DOI: 10.1126/sciadv.aau6468
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-catalyzed, P-directed selective C7 arylation of indoles

Abstract: We report a regioselective direct arylation of indoles at the C7 position with (hetero)aryl bromides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(23 citation statements)
references
References 71 publications
(73 reference statements)
0
23
0
Order By: Relevance
“…Intriguingly, the desired C7‐alkynylated indole 9 a was obtained in 65 % yield after the basic treatment of the crude reaction mixture, and no competing reaction on the pyrrole ring was observed. Other directing groups used in previous reports for the C7‐selective reactions, pivaloyl, phosphine, and phosphine oxide, were ineffective in the present alkynylation protocol.…”
Section: Methodsmentioning
confidence: 89%
“…Intriguingly, the desired C7‐alkynylated indole 9 a was obtained in 65 % yield after the basic treatment of the crude reaction mixture, and no competing reaction on the pyrrole ring was observed. Other directing groups used in previous reports for the C7‐selective reactions, pivaloyl, phosphine, and phosphine oxide, were ineffective in the present alkynylation protocol.…”
Section: Methodsmentioning
confidence: 89%
“…Taking advantage of the insights gained in substrate‐directed C−H borylation reactions, our group extended the available directing groups to phosphines. Our initial efforts in phosphine‐directed C−H borylation were reported in 2014, providing the first example of a general phosphine‐directed C−H functionalization and providing access to phosphine boronate esters from valuable phosphine precursors . The key to obtain the desired reactivity in these studies was running the reaction without added ligand.…”
Section: Methodsmentioning
confidence: 99%
“…The authors also demonstrated the C-5 arylation of indoles using different reaction protocols under the copper catalysis (Scheme 8). [25] The arylation of indoles is also well documented by the use of 4d metal catalysts like palladium, [26] rhodium, [27] ruthenium [28] Thearylation by these metals showed the excellent regiocontrol at mild reaction conditions compared to the 3d transition metals. Though the catalysts loading is almost similar, the employment of mild conditions is beneficial with the 4d metal catalysts.…”
Section: Cu-catalyzed Reactionsmentioning
confidence: 99%